The Analysis of Students’ Difficulties in Understanding Reading Questions in Textbooks - Regina Adellia Ong; Pratama Irwin Talenta (Magistra)
This study conducted to analyse the difficulties that students faced in understanding reading questions from their textbooks. The research aimed to explore these challenges and propose activities that could help students overcome them. The study employed a descriptive qualitative research design, providing a detailed description of the findings in a paragraph format. The participants in the research were 30 students from grade 5 and 6 at Mondial Primary School. To gather data, the researcher utilized two main instruments: a questionnaire and interviews. These tools were designed to collect information on the students' struggles and potential solutions to enhance their understanding of reading questions. The study identified three main difficulties faced by students: vocabulary, grammar, and comprehension of the questions themselves. This suggests that students may struggle with understanding the language used in the reading questions, the grammatical structure of the sentences, and the overall meaning of the questions posed in their textbooks. In response to these challenges, the researcher proposed two activities as potential solutions. The first is the use of "Pop Quiz," which is likely designed to test students' knowledge and understanding in a quick and interactive manner. The second activity mentioned is "Tongue Twister," which could be a fun and engaging way to improve pronunciation, vocabulary, and language skills. In summary, the study sheds light on the specific difficulties students faces in understanding reading questions and suggests practical activities, such as Pop Quiz and Tongue Twister, as potential interventions to address these challenges. The use of qualitative methods, including questionnaires and interviews, allowed the researcher to gain insights directly from the students involved in the study.